VISUAL STORYTELLING AND TRANSGENDER IDENTITY IN BOLLYWOOD: A CRITICAL ANALYSIS OF MISE-EN-SCÈNE IN “LAXMII” - Patel, Satish Kumar; Mishra, Shivendra Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper critically examines the Mise-en-scène of the 2020 Bollywood movie “Laxmii”, focusing on the transgender protagonist’s journey towards self-acceptance through visual elements like clothing, accessories, makeup, and hairstyles. Employing content analysis and drawing upon queer and representation theories. This research explores the visual elements that reflect both Laxmii’s internal and external struggles, emphasizing the cultural and spiritual dimensions that influence her transformation. The analysis shows that Laxmii’s shift from a white shirt and blue shorts to a red saree symbolizes her progression from societal conformity to self-empowerment. Accessories like red bangles, earrings, nose pins and anklets reinforce her traditional femininity, while her medium-length hairstyle reflects her fluid gender identity. The transition in makeup, from natural to bold, emphasizes her acceptance of her true self and spiritual awakening. The film’s integration of cultural and spiritual motifs enriches the portrayal of transgender identity, blending traditional symbols with Laxmii’s personal journey. Laxmii movie employs powerful visual storytelling to not only portray transgender identity but also foster a deeper understanding of the challenges and experiences faced by transgender individuals in Indian society.